2006
DOI: 10.1111/j.1365-2699.2006.01594.x
|View full text |Cite
|
Sign up to set email alerts
|

ORIGINAL ARTICLE: Predicting species distributions from small numbers of occurrence records: a test case using cryptic geckos in Madagascar

Abstract: Aim Techniques that predict species potential distributions by combining observed occurrence records with environmental variables show much potential for application across a range of biogeographical analyses. Some of the most promising applications relate to species for which occurrence records are scarce, due to cryptic habits, locally restricted distributions or low sampling effort. However, the minimum sample sizes required to yield useful predictions remain difficult to determine. Here we developed and te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

45
2,343
1
147

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 2,701 publications
(2,536 citation statements)
references
References 69 publications
45
2,343
1
147
Order By: Relevance
“…Populations located in the northern subtropical and mid-subtropical humid areas may experience greater precipitation and temperature under climate change [74]; this situation was predicted in our study as we concluded that Bio12 (annual precipitation) and Bio1 (annual mean air temperature) were the major bioclimatic variables contributing to the potential suitable habitat geographic distribution areas. Results consistent with previous studies indicate that trees located on the southern edge of their distributional range are expected to display growth declines, while increased growth is anticipated for those on the northern edge [19,64,[75][76][77].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Populations located in the northern subtropical and mid-subtropical humid areas may experience greater precipitation and temperature under climate change [74]; this situation was predicted in our study as we concluded that Bio12 (annual precipitation) and Bio1 (annual mean air temperature) were the major bioclimatic variables contributing to the potential suitable habitat geographic distribution areas. Results consistent with previous studies indicate that trees located on the southern edge of their distributional range are expected to display growth declines, while increased growth is anticipated for those on the northern edge [19,64,[75][76][77].…”
Section: Discussionsupporting
confidence: 89%
“…MaxEnt is a presence-background algorithm which calculates the probability of habitat suitability, based on the occurrence locations relative to random background conditions [62][63][64]. The occurrence locations define the environmental constraints placed on the predicted distribution.…”
Section: Development Of Climate Niche Models and Projections For Futumentioning
confidence: 99%
“…To explore these points in greater detail, we developed a Maxent ENM based on all available occurrence data and all environmental dimensions proven informative in the jackknife tests. This model was converted from continuous to binary based on the least training presence threshold approach of Pearson et al (2007). This model prediction was then combined (Grid Combine option, ArcGIS, version 9.2, ESRI, Redlands, California, USA) with the environmental coverages on which it was based to create a raster GIS coverage with an associated attributes table summarizing the predictions and all combinations of environmental conditions.…”
Section: Characterization Of Distributions and Ecologic Nichesmentioning
confidence: 99%
“…Because the spatial resolution of ENMs is limited only by the spatial precision of the occurrence and environmental data, the resulting picture is much more refined . Niche modeling approaches are applicable even when sample sizes are relatively small (Pearson et al, 2007) as demonstrated in analyses of the geography of Marburg virus transmission to humans (Peterson et al, 2006a). Niche models also permit exploration of the potential geography and ecology of pathogen transmission across novel landscapes (Peterson, 2003).…”
Section: Diseases and Niche Modelingmentioning
confidence: 99%
“…Both indexes range from 0 (no overlap in environmental use) to 1 (complete overlap in environmental use). For the background similarity test, we developed 100 replicate comparisons of each population's known occurrences against the background (points drawn from the accessible area) of the other (sample sizes matching those available for the "background" population), thresholded all models using E = 10% (Pearson et al, 2007) and compared observed similarities (i.e. between models based on actual occurrences) with replicate observed-background distributions.…”
Section: Niche Modelsmentioning
confidence: 99%